(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the preservation, study and reintegration of early historical audio recordings of traditional music from the Turkic world. Many of these recordings remain fragmented and underexplored. Recorded by European researchers in the early twentieth century, these phonographic materials represent invaluable cultural, historical and scholarly resources. Today, they are housed in major sound archives, including those in Vienna, Berlin, Paris, Budapest and St. Petersburg. However, most remain insufficiently studied and inaccessible to the communities they represent. Of particular significance are the unique field and prisoner-of-war recordings made between 1902 and 1944 which document the voices of Turkic-speaking individuals in historically complex and ethically sensitive conditions. Drawing on recent research conducted within the ICTMD–TURKSOY initiative, ‘The Phonogram Archive of the Turkic World’, this article outlines the methodology of cross-referencing multilingual archival data to identify performers and analyse accompanying metadata. It also discusses current efforts to digitise these materials, interpret them from a scholarly perspective, and integrate them into contemporary academic and cultural discourse. Ultimately, this work contributes to heritage preservation, historical justice, and the re-establishment of cultural memory for the Turkic world.